2019
DOI: 10.1002/cam4.2044
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal therapy in uterine sarcomas

Abstract: Uterine sarcomas (USs) are a group of rare but aggressive uterine malignancies, accounting for only 1% of the malignant tumors of female reproductive organs. Due to the high rate of recurrence and metastasis, the prognosis of USs is poor. Given the high mortality rate and limited clinical benefit of surgery and adjuvant chemoradiotherapy, hormonal therapy has shown good prospects in recent years. Hormonal agents include progestins, aromatase inhibitors (AIs), and gonadotropin‐releasing hormone analogue (GnRH‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…In doing so, Beatson leveraged on the connection between sex steroid hormones and cancer (Beatson, 1896), thereby paving to way to hormonal therapy in hormone-sensitive cancers (such as breast, ovarian, endometrial, and prostate cancers). This treatment modality became later a widely deployed strategy, still in use today (Shevach et al, 2019;Zang et al, 2019). Nonetheless, the underlying link between hormones, inflammation, and cancer began to unravel only more recently (Gharwan et al, 2015;Key, 1995;Mantovani et al, 2008;Ö zdemir and Dotto, 2019).…”
Section: The Dawn Of Tumor Immunologymentioning
confidence: 99%
“…In doing so, Beatson leveraged on the connection between sex steroid hormones and cancer (Beatson, 1896), thereby paving to way to hormonal therapy in hormone-sensitive cancers (such as breast, ovarian, endometrial, and prostate cancers). This treatment modality became later a widely deployed strategy, still in use today (Shevach et al, 2019;Zang et al, 2019). Nonetheless, the underlying link between hormones, inflammation, and cancer began to unravel only more recently (Gharwan et al, 2015;Key, 1995;Mantovani et al, 2008;Ö zdemir and Dotto, 2019).…”
Section: The Dawn Of Tumor Immunologymentioning
confidence: 99%
“…Xu et al reported 36 cases with good outcome after lobectomy in the majority of the cases 12 . Hormonal treatment is recommended given the established sensitivity of LGESS to these agents 12,37 . Our patient was treated with Anastrozole which to this day has stabilized her disease.…”
Section: Discussionmentioning
confidence: 72%
“…Yamaguchi et al suggested that Letrozole as well as progestins could be the first choice for patients with recurrent or residual low-grade endometrial stromal sarcoma (51). It seems that letrozole is the first-line hormone drug for postoperative adjuvant therapy in patients with stage I uterine leiomyosarcoma, while exemestane and anastrozole are for second-line treatment in patients with recurrent, metastatic and unresectable uterine leiomyosarcoma (52). In a clinical trial by George et al (53) of 27 postmenopausal women with metastatic and/or unresectable uterine leiomyosarcoma with positive estrogen receptors and/or postive progesteron receptors it has been found that the rate of stable disease was 54% in all patients and the 12-week rate of progression free survival 50%.…”
Section: Discussionmentioning
confidence: 99%